Assessment of the ecological bias of seven aggregate social deprivation indices - Josephine Bryere; Carole Pornet; Nane Copin; Ludivine Launay; Gaëlle Gusto; Pascale Grosclaude; Cyrille Delpierre; Thierry Lang; Olivier Lantieri; Olivier Dejardin; Guy Launoy (BMC, 2017)
Abstract Background In aggregate studies, ecological indices are used to study the influence of socioeconomic status on health. Their main limitation is ecological bias. This study assesses the misclassification of individual socioeconomic status in seven ecological indices. Methods Individual socioeconomic data for a random sample of 10,000 persons came from periodic health examinations conducted in 2006 in 11 French departments. Geographical data came from the 2007 census at the lowest geographical level available in France. The Receiver Operating Characteristics (ROC) curves, the areas under the curves (AUC) for each individual variable, and the distribution of deprived and non-deprived persons in quintiles of each aggregate score were analyzed. Results The aggregate indices studied are quite good "proxies" for individual deprivation (AUC close to 0.7), and they have similar performance. The indices are more efficient at measuring individual income than education or occupational category and are suitable for measuring of deprivation but not affluence. Conclusions The study inventoried the aggregate indices available in France and evaluated their assessment of individual SES.